2005
DOI: 10.1603/0022-0493-98.5.1614
|View full text |Cite
|
Sign up to set email alerts
|

A Test of High-Dose Verbenone for Stand-Level Protection of Lodgepole and Whitebark Pine from Mountain Pine Beetle (Coleoptera: Curculionidae: Scolytinae) Attacks

Abstract: The efficacy of verbenone as a stand-level protectant against mountain pine beetle, Dendroctonus ponderosae Hopkins, attacks was tested in lodgepole and whitebark pine stands at five geographically separated sites, including three consecutive years at one site. Forty and 20 high-dose pouches, with a verbenone emission rate up to 50 mg/d per pouch, were spaced in a grid pattern throughout 0.40-ha plots, replicated up to six times at each site. Although the verbenone treatment did not prevent beetles from disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
(37 reference statements)
3
22
3
Order By: Relevance
“…For all other relationships between percentage of red trees and percentage of available trees massattacked, the r 2 values ranged from .0012 to .3293 and the corresponding P values from 0.9239 to 0.0826. This result is in contrast to that found by Bentz et al (2005) in plots treated with high-dose verbenone at 10-m centres. However, Bentz et al (2005) found that verbenone treatment became ineffective when there were ≥ 200 red trees/ha, while the highest density of red trees/ha in our plots was 89 (Table 4).…”
Section: Mass Attackcontrasting
confidence: 99%
See 4 more Smart Citations
“…For all other relationships between percentage of red trees and percentage of available trees massattacked, the r 2 values ranged from .0012 to .3293 and the corresponding P values from 0.9239 to 0.0826. This result is in contrast to that found by Bentz et al (2005) in plots treated with high-dose verbenone at 10-m centres. However, Bentz et al (2005) found that verbenone treatment became ineffective when there were ≥ 200 red trees/ha, while the highest density of red trees/ha in our plots was 89 (Table 4).…”
Section: Mass Attackcontrasting
confidence: 99%
“…Because this was an operational evaluation designed to protect all PSPs to the maximum extent possible, no control plots were left untreated. However, the results are similar to those of Bentz et al (2005), who found that, when compared to control plots, high-dose verbenone protected most trees from attack, but that treatment efficacy was not uniformly consistent. Similarly, Progar (2003Progar ( , 2005 found that verbenone protected treated plots from attack for two successive years, but in the face of an advancing infestation, efficacy was lost thereafter.…”
Section: Evaluation Of the Push Tactic Using High-dose Verbenone Plussupporting
confidence: 83%
See 3 more Smart Citations